Moral distress in nurses: Resources and constraints, consequences, and interventions. (September 2022) - Ghazanfari, Mohammad Javad; Emami Zeydi, Amir; Panahi, Reza; Ghanbari, Reza; Jafaraghaee, Fateme; Mortazavi, Hamed; Karkhah, Samad
Background: Moral distress is a complex and challenging issue in the nursing profession that can negatively affect the nurses' job satisfaction and retention and the quality of patient care. This study focused on describing the resources and constraints, consequences, and interventions of moral distress in nurses. Methods: In a literature review, an extensive electronic search was conducted in databases including PubMed, ISI, Scopus as well as Google Scholar search engine using the keywords including "moral distress" and "nurses" to identify resources, constraints, consequences, and interventions about moral distress in nurses, from the earliest records up to 26 December 2020. The required data were extracted from 61 relevant studies by two independent reviewers. Results: Resources and constraints in the occurrence of moral distress among nurses can be divided into three general categories including internal factors, clinical factors, and external factors. The consequences of moral distress on nurses and the medical system reduced moral sensitivity, development of psychological and physical health problems, and the intention to leave the profession. The potential effective interventions were the implementation of integrated communication programs, strengthening physician–nurse collaboration, nursing involvement in clinical decision-making and end-of-life issues, social support, using a resiliency bundle, interdisciplinary discussion, and promoting nurses' ethical and communication skills. Conclusion: There are a wide range of resources and constraints impacting moral distress in nurses that could lead to negative consequences. Further studies are necessary to identify, evaluate, and implement a range of potential effective interventions for the management of moral distress in nurses.